Acid and alkali resistant glass and method for manufacturing the same

CN118637834BActive Publication Date: 2026-10-16JIANGSU HUAOU GLASS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410603431.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2026-10-16
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

二氧化硅具有较高的化学稳定性,具有一定的耐酸性,使得玻璃能够耐受一定浓度的酸性物质的侵蚀,但是氢氟酸和热磷酸能对玻璃产生剧烈腐蚀

Benefits of technology

[0032]This invention first adds 4,4'-diaminobenzoyl aniline to xylene and mixes thoroughly. Then, glass fiber and composite glass powder are added, and the mixture is stirred at room temperature. Next, hexafluorodianhydride is added, and the mixture is heated and stirred to obtain a modified polyamic acid slurry. A catalyst is then added, followed by imidization and post-treatment to obtain modified polyimide. The modified polyimide is then ultrasonically dispersed in N,N-dimethylformamide and subjected to vacuum degassing to obtain a coating solution. The surface of ordinary glass is etched to obtain pretreated glass. Finally, the coating solution is uniformly coated onto the surface of the pretreated glass, and heat-treated to obtain an acid and alkali resistant glass. The glass product obtained by this invention exhibits excellent acid and alkali resistance, expanding the application range of glass.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses acid and alkali resistant glass and a preparation method thereof. 4,4'-diamino benzoyl aniline is added into xylene, mixed uniformly, glass fiber and composite glass powder are continuously added, stirred at room temperature, hexafluorodianhydride is added, heated and stirred to react, modified polyamide acid slurry is obtained, a catalyst is added, imidization is carried out, post-treatment is carried out, and modified polyimide is obtained; then the modified polyimide is ultrasonically dispersed in N,N-dimethylformamide, vacuum defoaming treatment is carried out, and coating liquid is obtained; etching treatment is carried out on the surface of common glass, and pretreated glass is obtained; finally, the coating liquid is uniformly coated on the surface of the pretreated glass, and heat treatment is carried out. The glass product obtained by the application has excellent acid and alkali resistance, and the application range of the glass is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of glass processing technology, specifically relating to an acid and alkali resistant glass and its preparation method. Background Technology

[0002] Glass is an amorphous inorganic non-metallic material, typically made from a variety of inorganic minerals (such as quartz sand, borax, barite, barium carbonate, limestone, feldspar, etc.) as the main raw materials, with the addition of small amounts of auxiliary materials. The main components of glass are silicon dioxide and other oxides, which usually exist in the form of silicate double salts. Silicon dioxide has high chemical stability and a certain degree of acid resistance, allowing glass to withstand the erosion of certain concentrations of acidic substances. However, hydrofluoric acid and hot phosphoric acid can severely corrode glass. Silicon dioxide is an acidic oxide, exhibiting poor resistance to alkalis and alkaline salts, and can form soluble silicates with these reagents, thus limiting the application areas of glass.

[0003] Patent CN110240405B discloses an alkali-resistant aluminosilicate glass made from silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zirconium oxide, titanium dioxide, tantalum pentoxide, and yttrium oxide. This patent application primarily improves the alkali resistance of the glass by adjusting the raw material formulation; however, the alkali resistance can only meet the A1 standard and cannot satisfy higher alkali resistance requirements.

[0004] Patent CN103833220B discloses an alkali-resistant and heat-resistant glass material, which is made from a mixture of tellurium dioxide, potassium oxide, silicon dioxide, lead oxide, and yttrium trioxide. The glass material obtained by this patent, after being sprayed with a 10wt% sodium hydroxide solution and left for 40 to 60 hours, showed no corrosion. After being placed at 400℃ and 500℃ for 20 hours, it did not soften, indicating that its alkali resistance still has significant room for improvement. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide an acid and alkali resistant glass and its preparation method, which has excellent acid and alkali resistance and expands the application range of glass.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0008] (1) By weight, 5-8 parts of quartz sand, 3-4 parts of dolomite, 2-3 parts of borocalcite, 1-2 parts of magnesium olivine, 0.8-1 parts of bauxite, and 0.8-1 parts of sodium carbonate are used as raw materials. The raw materials are melted, drawn through a stencil, and cooled after fiber forming.

[0009] (2) Then add 4,4'-diaminobenzoyl aniline to xylene, mix evenly, and continue to add the glass fiber and composite glass powder obtained in step (1), stir at room temperature, then add hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide.

[0010] (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0011] (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0012] Preferably, in step (1), the particle size of the raw material is 200-300 mesh.

[0013] Preferably, in step (1), each raw material is weighed, water is added and mixed to obtain a mixture with a water content of 2-3 wt%, and then it is melted.

[0014] Preferably, in step (1), the melting process conditions are: 1450~1550℃ for 3~4 hours and 1350~1400℃ for 1~2 hours.

[0015] Preferably, in step (1), the wire drawing temperature of the stencil is 1250-1350℃.

[0016] Preferably, in step (1), the cooling process conditions are: water pressure 0.2-0.3 MPa, air pressure 0.2-0.3 MPa, and the spray cone angle is fully open, with an opening angle of 70-80°.

[0017] Preferably, in step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 2 to 5 μm.

[0018] More preferably, the Ca-Si-B series glass powder is obtained by mixing and grinding calcium oxide, silicon dioxide, aluminum oxide, boric acid and tellurium dioxide in a mass ratio of 5-7:2-3:2-3:3-5:1-2 until uniform, melting at 1350-1400℃ for 1-2 hours, water quenching, refining, sieving and drying.

[0019] More preferably, the Nb-Zn-B-Si glass powder is obtained by mixing and grinding niobium pentoxide, zinc oxide, silicon dioxide, boron oxide, molybdenum trioxide, tellurium dioxide, and sodium oxide in a mass ratio of 8-10:15-20:30-40:8-10:2-3:2-3:5-7 until uniform, melting at 1400-1500℃ for 1-2 hours, water quenching, refining, sieving, and drying.

[0020] Preferably, in step (2), the mass ratio of 4,4'-diaminobenzoyl aniline, xylene, glass fiber, composite glass powder, and hexafluorodianhydride is 1:6-8:0.1-0.2:0.2-0.3:1.2-1.5.

[0021] Preferably, in step (2), the stirring time at room temperature is 2 to 3 hours; the temperature of the heating and stirring reaction is 60 to 70°C, and the time is 5 to 7 hours.

[0022] Preferably, in step (2), the amount of catalyst used is 1 to 2% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0023] Preferably, in step (2), the imidization process conditions are: reaction at 90-95°C for 8-10 hours.

[0024] Preferably, in step (2), the post-processing includes: filtering to obtain the solid, washing with xylene 3 to 5 times, and drying.

[0025] Preferably, in step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4-5; and the vacuum degassing treatment time is 3-4 hours.

[0026] Preferably, in step (3), the ultrasonic dispersion process conditions are: ultrasonic dispersion at 300-400W for 30-40 minutes.

[0027] Preferably, in step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned sequentially with trichloroethylene, acetone, anhydrous ethanol, and deionized water, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 65-75°C for 2-3 hours, then taken out, washed with water, and dried. The etching solution is obtained by mixing potassium hydroxide, carrageenan, gelatin, and glycerin in a mass ratio of 10:2-3:2-3:3-4.

[0028] Further preferred ultrasonic cleaning process conditions are: 300-400W ultrasonic cleaning for 20-30 minutes.

[0029] Preferably, in step (4), the coating amount of the coating liquid is 20-30 g / m². 2 The heat treatment process conditions are: heat treatment at 220-250℃ for 2-3 hours.

[0030] An acid and alkali resistant glass is obtained by the aforementioned preparation method.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] This invention first adds 4,4'-diaminobenzoyl aniline to xylene and mixes thoroughly. Then, glass fiber and composite glass powder are added, and the mixture is stirred at room temperature. Next, hexafluorodianhydride is added, and the mixture is heated and stirred to obtain a modified polyamic acid slurry. A catalyst is then added, followed by imidization and post-treatment to obtain modified polyimide. The modified polyimide is then ultrasonically dispersed in N,N-dimethylformamide and subjected to vacuum degassing to obtain a coating solution. The surface of ordinary glass is etched to obtain pretreated glass. Finally, the coating solution is uniformly coated onto the surface of the pretreated glass, and heat-treated to obtain an acid and alkali resistant glass. The glass product obtained by this invention exhibits excellent acid and alkali resistance, expanding the application range of glass.

[0033] The glass fiber of this invention is obtained by using quartz sand, dolomite, borosilicate, forsterite, bauxite, sodium carbonate, etc., as raw materials, through melting, stencil drawing, and cooling after fiber formation. The applicant has adjusted the raw material formula to prepare glass fibers with good acid and alkali resistance.

[0034] The composite glass powder of the present invention is obtained by mixing Ca-Si-B system glass powder and Nb-Zn-B-Si system glass powder in equal mass, and also has good acid and alkali resistance.

[0035] In the reaction system for preparing polyamic acid by reacting 4,4'-diaminobenzoyl aniline with hexafluorodianhydride, glass fiber and composite glass powder are added to obtain modified polyamic acid, which is then further imidized to obtain modified polyimide with excellent acid and alkali resistance.

[0036] After ordinary glass is etched, the surface is roughened. After the coating liquid is applied, the modified polyimide is fully filled. During the heat treatment process, the glass fiber and composite glass powder are fully compatible with the pretreated glass and have strong bonding force, thereby effectively improving the acid and alkali resistance of the glass product. Detailed Implementation

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0038] The ordinary glass used in the examples and comparative examples was purchased from Tianjin Baisheng Glass Co., Ltd., and its size was 1m×1m×5mm.

[0039] Unless otherwise specified, all products in this invention were purchased through market channels.

[0040] Example 1

[0041] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0042] (1) First, 0.5 kg of quartz sand, 0.3 kg of dolomite, 0.2 kg of borate, 0.1 kg of forsterite, 0.08 kg of bauxite and 0.08 kg of sodium carbonate are used as raw materials. Glass fiber is prepared by melting, drawing with a stencil, forming the fiber and cooling it.

[0043] (2) Then add 1 kg of 4,4'-diaminobenzoyl aniline to 6 kg of xylene, mix evenly, add 0.1 kg of glass fiber and 0.2 kg of composite glass powder, stir at room temperature, add 1.2 kg of hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide.

[0044] (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0045] (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0046] In step (1), each raw material is weighed, the particle size of the raw material is 200 mesh, water is added and mixed to obtain a mixture with a water content of 2wt%, and then it is melted.

[0047] The melting process conditions are: 1450℃ for 3 hours and 1350℃ for 1 hour.

[0048] The stencil drawing temperature is 1250℃.

[0049] The cooling process conditions are: water pressure 0.2MPa, air pressure 0.2MPa, spray cone fully open, with an opening angle of 70°.

[0050] In step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 2μm.

[0051] The Ca-Si-B series glass powder is obtained by mixing and grinding 0.5 kg of calcium oxide, 0.2 kg of silicon dioxide, 0.2 kg of aluminum oxide, 0.3 kg of boric acid and 0.1 kg of tellurium dioxide evenly, melting at 1350℃ for 1 hour, water quenching, refining, sieving and drying.

[0052] The Nb-Zn-B-Si glass powder is obtained by mixing and grinding 0.8 kg of niobium pentoxide, 1.5 kg of zinc oxide, 3 kg of silicon dioxide, 0.8 kg of boron oxide, 0.2 kg of molybdenum trioxide, 0.2 kg of tellurium dioxide, and 0.5 kg of sodium oxide evenly, melting at 1400℃ for 1 hour, water quenching, refining, sieving, and drying.

[0053] The stirring time at room temperature is 2 hours; the heating and stirring reaction temperature is 60℃ and the time is 5 hours.

[0054] The amount of catalyst used is 1% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0055] The imidization process conditions are: reaction at 90℃ for 8 hours.

[0056] Post-processing includes: filtering to obtain the solid, washing three times with xylene, and drying.

[0057] In step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4; the vacuum degassing treatment time is 3 hours.

[0058] The ultrasonic dispersion process conditions are: ultrasonic dispersion at 300W for 30 minutes.

[0059] In step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned with trichloroethylene, acetone, anhydrous ethanol and deionized water in sequence, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 65°C for 2 hours, then taken out, washed with water and dried. The etching solution is prepared by stirring and mixing 10 kg potassium hydroxide, 2 kg carrageenan, 2 kg gelatin and 3 kg glycerin.

[0060] The ultrasonic cleaning process conditions are: 300W ultrasonic cleaning for 20 minutes.

[0061] The coating amount of the coating liquid is 20 g / m². 2 The heat treatment process conditions are: heat treatment at 220℃ for 2 hours.

[0062] Example 2

[0063] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0064] (1) First, 0.8 kg of quartz sand, 0.4 kg of dolomite, 0.3 kg of borate, 0.2 kg of forsterite, 0.1 kg of bauxite and 0.1 kg of sodium carbonate are used as raw materials. Glass fibers are prepared by melting, drawing with a stencil, forming the fibers and cooling them.

[0065] (2) Then add 1 kg of 4,4'-diaminobenzoyl aniline to 8 kg of xylene, mix evenly, add 0.2 kg of glass fiber and 0.3 kg of composite glass powder, stir at room temperature, add 1.5 kg of hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide.

[0066] (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0067] (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0068] In step (1), each raw material is weighed, the particle size of the raw material is 300 mesh, water is added and mixed evenly to obtain a mixture with a water content of 3wt%, and then it is melted.

[0069] The melting process conditions are: 1550℃ for 4 hours and 1400℃ for 2 hours.

[0070] The stencil drawing temperature is 1350℃.

[0071] The cooling process conditions are: water pressure 0.3MPa, air pressure 0.3MPa, spray cone fully open, with an opening angle of 80°.

[0072] In step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 5 μm.

[0073] The Ca-Si-B series glass powder is obtained by mixing and grinding 0.7 kg of calcium oxide, 0.3 kg of silicon dioxide, 0.3 kg of aluminum oxide, 0.5 kg of boric acid and 0.2 kg of tellurium dioxide evenly, melting at 1400℃ for 2 hours, water quenching, refining, sieving and drying.

[0074] The Nb-Zn-B-Si glass powder is obtained by mixing and grinding 1 kg of niobium pentoxide, 2 kg of zinc oxide, 4 kg of silicon dioxide, 1 kg of boron oxide, 0.3 kg of molybdenum trioxide, 0.3 kg of tellurium dioxide, and 0.7 kg of sodium oxide evenly, melting at 1500℃ for 2 hours, water quenching, refining, sieving, and drying.

[0075] The stirring time at room temperature is 3 hours; the heating and stirring reaction temperature is 70℃ and the time is 7 hours.

[0076] The amount of catalyst used is 2% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0077] The imidization process conditions are: reaction at 95℃ for 10 hours.

[0078] Post-processing includes: filtering to obtain the solid, washing five times with xylene, and drying.

[0079] In step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:5; the vacuum degassing treatment time is 4 hours.

[0080] The ultrasonic dispersion process conditions are: ultrasonic dispersion at 400W for 40 minutes.

[0081] In step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned with trichloroethylene, acetone, anhydrous ethanol and deionized water in sequence, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 75°C for 3 hours, taken out and washed with water, and then dried. The etching solution is prepared by stirring and mixing 10 kg of potassium hydroxide, 3 kg of carrageenan, 3 kg of gelatin and 4 kg of glycerin.

[0082] The ultrasonic cleaning process conditions are: 400W ultrasonic cleaning for 30 minutes.

[0083] The coating amount of the coating liquid is 30g / m². 2 The heat treatment process conditions are: heat treatment at 250℃ for 3 hours.

[0084] Example 3

[0085] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0086] (1) First, 0.5 kg of quartz sand, 0.4 kg of dolomite, 0.2 kg of borate, 0.2 kg of forsterite, 0.08 kg of bauxite and 0.1 kg of sodium carbonate are used as raw materials. Glass fiber is prepared by melting, drawing with a stencil, forming the fiber and cooling it.

[0087] (2) Then add 1 kg of 4,4'-diaminobenzoyl aniline to 6 kg of xylene, mix evenly, add 0.2 kg of glass fiber and 0.2 kg of composite glass powder, stir at room temperature, add 1.5 kg of hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide.

[0088] (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0089] (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0090] In step (1), each raw material is weighed, the particle size of the raw material is 200 mesh, water is added and mixed to obtain a mixture with a water content of 3wt%, and then it is melted.

[0091] The melting process conditions are: 1450℃ for 4 hours and 1350℃ for 2 hours.

[0092] The stencil drawing temperature is 1250℃.

[0093] The cooling process conditions are: water pressure 0.3MPa, air pressure 0.2MPa, spray cone fully open, with an opening angle of 80°.

[0094] In step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 2μm.

[0095] The Ca-Si-B series glass powder is obtained by mixing and grinding 0.7 kg of calcium oxide, 0.2 kg of silicon dioxide, 0.3 kg of aluminum oxide, 0.3 kg of boric acid and 0.2 kg of tellurium dioxide evenly, melting at 1350℃ for 2 hours, water quenching, refining, sieving and drying.

[0096] The Nb-Zn-B-Si glass powder is obtained by mixing and grinding 0.8 kg of niobium pentoxide, 2 kg of zinc oxide, 3 kg of silicon dioxide, 1 kg of boron oxide, 0.2 kg of molybdenum trioxide, 0.3 kg of tellurium dioxide, and 0.5 kg of sodium oxide evenly, melting at 1500℃ for 1 hour, water quenching, refining, sieving, and drying.

[0097] The stirring time at room temperature is 3 hours; the heating and stirring reaction temperature is 60℃ and the time is 7 hours.

[0098] The amount of catalyst used is 1% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0099] The imidization process conditions were: reaction at 95°C for 8 hours.

[0100] Post-processing includes: filtering to obtain the solid, washing five times with xylene, and drying.

[0101] In step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4; the vacuum degassing treatment time is 4 hours.

[0102] The ultrasonic dispersion process conditions are: ultrasonic dispersion at 300W for 40 minutes.

[0103] In step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned with trichloroethylene, acetone, anhydrous ethanol and deionized water in sequence, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 65°C for 3 hours, taken out and washed with water, and then dried. The etching solution is prepared by stirring and mixing 10 kg of potassium hydroxide, 2 kg of carrageenan, 3 kg of gelatin and 3 kg of glycerin.

[0104] The ultrasonic cleaning process conditions are: 400W ultrasonic cleaning for 20 minutes.

[0105] The coating amount of the coating liquid is 30g / m². 2 The heat treatment process conditions are: heat treatment at 220℃ for 3 hours.

[0106] Example 4

[0107] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0108] (1) First, 0.6 kg of quartz sand, 0.3 kg of dolomite, 0.25 kg of borate, 0.15 kg of forsterite, 0.09 kg of bauxite and 0.09 kg of sodium carbonate are used as raw materials. Glass fiber is prepared by melting, drawing with a stencil, forming the fiber and cooling it.

[0109] (2) Then add 1 kg of 4,4'-diaminobenzoyl aniline to 7 kg of xylene, mix evenly, add 0.15 kg of glass fiber and 0.25 kg of composite glass powder, stir at room temperature, add 1.3 kg of hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide;

[0110] (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0111] (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0112] In step (1), each raw material is weighed, the particle size of the raw material is 300 mesh, water is added and mixed to obtain a mixture with a water content of 2.5 wt%, and then it is melted.

[0113] The melting process conditions are: 1500℃ for 3.5 hours and 1400℃ for 1.5 hours.

[0114] The stencil drawing temperature is 1300℃.

[0115] The cooling process conditions are: water pressure 0.2MPa, air pressure 0.2MPa, spray cone fully open, with an opening angle of 75°.

[0116] In step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 3μm.

[0117] The Ca-Si-B series glass powder is obtained by mixing and grinding 0.6 kg of calcium oxide, 0.25 kg of silicon dioxide, 0.25 kg of aluminum oxide, 0.4 kg of boric acid and 0.15 kg of tellurium dioxide evenly, melting at 1380℃ for 1.5 hours, water quenching, refining, sieving and drying.

[0118] The Nb-Zn-B-Si glass powder is obtained by mixing and grinding 0.9 kg of niobium pentoxide, 1.8 kg of zinc oxide, 3.5 kg of silicon dioxide, 0.9 kg of boron oxide, 0.25 kg of molybdenum trioxide, 0.25 kg of tellurium dioxide, and 0.6 kg of sodium oxide evenly, melting at 1450℃ for 1.5 hours, water quenching, refining, sieving, and drying.

[0119] The stirring time at room temperature was 2.5 hours; the reaction temperature was 65℃ and the stirring time was 6 hours.

[0120] The amount of catalyst used is 1.5% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0121] The imidization process conditions were: reaction at 92℃ for 9 hours.

[0122] Post-processing includes: filtering to obtain the solid, washing with xylene four times, and drying.

[0123] In step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4.5; the vacuum degassing treatment time is 3.5 hours.

[0124] The ultrasonic dispersion process conditions are: ultrasonic dispersion at 400W for 35 minutes.

[0125] In step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned in sequence with trichloroethylene, acetone, anhydrous ethanol and deionized water, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 70°C for 2 hours, then taken out, washed with water and dried. The etching solution is prepared by stirring and mixing 10 kg of potassium hydroxide, 2.5 kg of carrageenan, 2.5 kg of gelatin and 3.5 kg of glycerin.

[0126] The ultrasonic cleaning process conditions are: 400W ultrasonic cleaning for 25 minutes.

[0127] The coating amount of the coating liquid is 25 g / m².2 The heat treatment process conditions are: heat treatment at 230℃ for 2.5 hours.

[0128] Comparative Example

[0129] A method for preparing acid and alkali resistant glass, the specific steps of which are as follows:

[0130] (1) First, add 1 kg of 4,4'-diaminobenzoyl aniline to 6 kg of xylene, mix evenly, then add 0.2 kg of composite glass powder, stir at room temperature, then add 1.2 kg of hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-treat to obtain modified polyimide.

[0131] (2) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution;

[0132] (3) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass.

[0133] In step (1), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 2μm.

[0134] The Ca-Si-B series glass powder is obtained by mixing and grinding 0.5 kg of calcium oxide, 0.2 kg of silicon dioxide, 0.2 kg of aluminum oxide, 0.3 kg of boric acid and 0.1 kg of tellurium dioxide evenly, melting at 1350℃ for 1 hour, water quenching, refining, sieving and drying.

[0135] The Nb-Zn-B-Si glass powder is obtained by mixing and grinding 0.8 kg of niobium pentoxide, 1.5 kg of zinc oxide, 3 kg of silicon dioxide, 0.8 kg of boron oxide, 0.2 kg of molybdenum trioxide, 0.2 kg of tellurium dioxide, and 0.5 kg of sodium oxide evenly, melting at 1400℃ for 1 hour, water quenching, refining, sieving, and drying.

[0136] The stirring time at room temperature is 2 hours; the heating and stirring reaction temperature is 60℃ and the time is 5 hours.

[0137] The amount of catalyst used is 1% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate.

[0138] The imidization process conditions are: reaction at 90℃ for 8 hours.

[0139] Post-processing includes: filtering to obtain the solid, washing three times with xylene, and drying.

[0140] In step (2), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4; the vacuum degassing treatment time is 3 hours.

[0141] The ultrasonic dispersion process conditions are: ultrasonic dispersion at 300W for 30 minutes.

[0142] In step (3), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned with trichloroethylene, acetone, anhydrous ethanol and deionized water in sequence, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 65°C for 2 hours, then taken out, washed with water and dried. The etching solution is prepared by stirring and mixing 10 kg of potassium hydroxide, 2 kg of carrageenan, 2 kg of gelatin and 3 kg of glycerin.

[0143] The ultrasonic cleaning process conditions are: 300W ultrasonic cleaning for 20 minutes.

[0144] The coating amount of the coating liquid is 20 g / m². 2 The heat treatment process conditions are: heat treatment at 220℃ for 2 hours.

[0145] Test case

[0146] The glass obtained in Examples 1-4 and the comparative example were subjected to acid and alkali resistance tests, respectively.

[0147] Acid treatment: Immerse the glass completely in a 10% sulfuric acid solution and seal it for one week.

[0148] Alkali treatment: Immerse the glass completely in a 10% sodium hydroxide solution and seal it for one week.

[0149] The flexural strength of the glass was tested before and after acid treatment and alkali treatment, respectively. The specific methods are as follows:

[0150] The test was conducted at room temperature using the three-point method. The sample was placed on two supports at a certain distance apart, with a load applied at the center point of the supports. The maximum bending stress at breakage was measured. The test conditions were: indenter diameter 6mm, pressing speed 1mm / min, and span 30mm. The stress was calculated using the following formula: σ=3L×F / (2Wt) 2 ), where σ is the three-point bending strength (MPa), L is the span between the two supports (mm), F is the maximum bending stress when the sample breaks (N), W is the sample width (mm), and t is the sample thickness (mm).

[0151] The test results are shown in Table 1.

[0152] Table 1. Test results of acid and alkali resistance of glass

[0153] Example 1 109 105 103 Example 2 110 106 105 Example 3 112 109 108 Example 4 116 114 114 Comparative Example 98 85 80

[0154] As shown in Table 1, the glasses obtained in Examples 1 to 4 have very good acid and alkali resistance.

[0155] In the comparative example, omitting the glass fiber resulted in a decrease in the initial bending strength of the glass. The bending strength deteriorated significantly after acid and alkali treatments, indicating that the synergistic effect of glass fiber and composite glass powder, combined with the polyimide structure, improves the mechanical properties and acid and alkali resistance of the product.

[0156] The present invention has been illustrated through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of individual raw materials in the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing acid and alkali resistant glass, characterized in that, The specific steps are as follows: (1) By weight, 5-8 parts of quartz sand, 3-4 parts of dolomite, 2-3 parts of borocalcite, 1-2 parts of magnesium olivine, 0.8-1 parts of bauxite, and 0.8-1 parts of sodium carbonate are used as raw materials. The raw materials are melted, drawn through a stencil, and cooled after fiber forming. (2) Then add 4,4'-diaminobenzoyl aniline to xylene, mix evenly, and continue to add the glass fiber and composite glass powder obtained in step (1), stir at room temperature, then add hexafluorodianhydride, heat and stir to react, and obtain modified polyamic acid slurry. Then add catalyst, imidize, and post-process to obtain modified polyimide. (3) Then the modified polyimide was ultrasonically dispersed in N,N-dimethylformamide and vacuum degassing was performed to obtain the coating solution; (4) The surface of ordinary glass is etched to obtain pretreated glass; finally, a coating liquid is uniformly coated on the surface of the pretreated glass and heat-treated to obtain the acid and alkali resistant glass. In step (2), the composite glass powder is obtained by mixing Ca-Si-B glass powder and Nb-Zn-B-Si glass powder in equal mass, with a particle size of 2 to 5 μm; The Ca-Si-B series glass powder is obtained by mixing and grinding calcium oxide, silicon dioxide, aluminum oxide, boric acid and tellurium dioxide in a mass ratio of 5-7:2-3:2-3:3-5:1-2, melting at 1350-1400℃ for 1-2 hours, water quenching, refining, sieving and drying. The Nb-Zn-B-Si glass powder is obtained by mixing and grinding niobium pentoxide, zinc oxide, silicon dioxide, boron oxide, molybdenum trioxide, tellurium dioxide, and sodium oxide in a mass ratio of 8-10:15-20:30-40:8-10:2-3:2-3:5-7 until uniform, melting at 1400-1500℃ for 1-2 hours, water quenching, refining, sieving, and drying. In step (2), the mass ratio of 4,4'-diaminobenzoyl aniline, xylene, glass fiber, composite glass powder, and hexafluorodianhydride is 1:6-8:0.1-0.2:0.2-0.3:1.2-1.

5.

2. The preparation method according to claim 1, characterized in that, In step (1), each raw material is weighed, water is added and mixed to obtain a mixture with a water content of 2-3 wt%, and then it is melted.

3. The preparation method according to claim 1, characterized in that, In step (1), the melting process conditions are: 1450~1550℃ for 3~4 hours and 1350~1400℃ for 1~2 hours.

4. The preparation method according to claim 1, characterized in that, In step (1), the stencil drawing temperature is 1250~1350℃; The cooling process conditions are: water pressure 0.2-0.3 MPa, air pressure 0.2-0.3 MPa, spray cone fully open, with an opening angle of 70-80°.

5. The preparation method according to claim 1, characterized in that, In step (2), the stirring time at room temperature is 2 to 3 hours; the temperature for heating and stirring is 60 to 70°C, and the time is 5 to 7 hours. The amount of catalyst used is 1-2% of the mass of the modified polyamic acid slurry, and the catalyst is tripolyphosphate; The imidization process conditions are: reaction at 90–95°C for 8–10 hours; Post-processing includes: filtering to obtain the solid, washing with xylene 3 to 5 times, and drying.

6. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of modified polyimide to N,N-dimethylformamide is 1:4-5; the vacuum degassing treatment time is 3-4 hours; The ultrasonic dispersion process conditions are: ultrasonic dispersion at 300-400W for 30-40 minutes.

7. The preparation method according to claim 1, characterized in that, In step (4), the specific method of etching is as follows: First, ordinary glass is ultrasonically cleaned in sequence with trichloroethylene, acetone, anhydrous ethanol and deionized water, dried, and then completely immersed in the etching solution. Under sealed conditions, it is left to stand at 65-75°C for 2-3 hours. After removal, it is washed with water and dried. The etching solution is obtained by stirring and mixing potassium hydroxide, carrageenan, gelatin and glycerin in a mass ratio of 10:2-3:2-3:3-4.

8. An acid and alkali resistant glass, characterized in that, It is obtained by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • An alkali- and heat-resistant glass material and its preparation method

    CN103833220B

  • An Alkali-Resistant Aluminosilicate Glass and Its Applications

    CN110240405B

  • Superfine glass fiber, preparation method and application thereof, and polyimide film

    CN110903504A

  • Quartz glass tube with corrosion-resistant film on surface

    CN114455854A